Analisis Laporan Keuangan Pengelolaan Limbah Kelapa Sawit Pada PT. Perkebunan Nusantara III Persero Labuhanbatu Selatan - Ashari, Fara Sofia; Amini, Aisyah; Lubis, Adlin Nahar; Silalahi, Purnama Ramadani (Universitas Labuhanbatu, 2022)
The Mamikos application is a fairly good boarding house marketing application. However, this application has not been widely used by boarding house seekers in the city of Medan. This study aims to analyze the effectiveness of the Mamikos application in increasing visitors and boarding houses in the city of Medan. This study used a descriptive qualitative approach with data collection using in-depth interviews. Informants in this study are boarding houses in the city of Medan. The results of this study are that there are many platforms that boarding house owners can try, namely one of the best platforms is Mamikos. Using Mamikos makes it easier for boarding house owners in the city of Medan in marketing activities, room management, to property standardization in order to increase selling value. Boarding house seekers don't have to do a survey to find the place they want to live. Mamikos comes with many features provided, starting from direct bookings, chat features with tenants, digital payment methods and many other features.